Density‐Driven Migration of Heavy NAPL Vapor in the Unsaturated Zone. Issue 8 (21st August 2015) - Kleinknecht, Simon M.; Class, Holger; Braun, Jürgen
Abstract : Contaminant vapor (gas) plumes emanating from liquid sources migrate easily in the unsaturated zone. Heavy vapors preferentially migrate downward due to their greater density and thus pose a potential threat to underlying aquifers. Large‐scale column experiments and numerical simulations were conducted to investigate the density‐driven migration of carbon disulfide (CS2 ) vapor. Carbon disulfide, among others used to manufacture viscous rayon, is an industrial, non‐polar solvent. It is highly volatile and characterized by a very high density (1.6) relative to air when in a gaseous state. The experiments were conducted in large, vertical columns (i.d. = 0.109 m) of 4‐m length packed with a dry porous medium. Different types of glass beads were used to investigate the sensitivity of migration to permeability. The porous medium was kept dry to avoid partitioning effects into pore water. Gas samples were taken along the column throughout the experiment to quantify time and space dependent vapor migration. The experiments characterized the migration behavior of a heavy CS2 vapor plume injected in the middle of the column. The vapor plume steadily migrated downward dependent on the total mass of injected CS2 and permeability. The setup of the experiment was reproduced in a 1‐D, two‐phase, two‐component, isothermal, numerical model. Simulation results were compared with data from the vapor migration experiments. The results of the numerical model satisfactorily reproduced the migration behavior observed in the experiments but suggested slightly higher velocities than those observed. Thus the research presented improves the understanding of density driven, advective migration of a heavy contaminant vapor in a dry porous medium at a large scale. It provides valuable experimental data not only for future research but particularly for the transfer to field situations.